Set Up Reduction On Sheet Metal Fabrication Company C's CNC Punching Section - Loh, Hong Yi (Universiti Sains Malaysia, 2017)
To stand up in today’s globalization world, manufacturers are searching for alternative to reduce production time and cost to improve operating performance. As set up time is non-value added process to customers, manufacturers want to reduce set up time in their operation as low as near to zero. Company C, a sheet metal manufacturer want to achieve the same thing. This project is aim to provide positive result or impact on reduction of set up time in Company C’s CNC Punching operation. The objective of this project is to minimize trip to get material by operator and to minimize need of re-calibrate of die during set up.